2013
DOI: 10.4269/ajtmh.12-0695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Surveillance as Monitoring Tool for Drug-Resistant Plasmodium falciparum in Suriname

Abstract: Abstract. The aim of this translational study was to show the use of molecular surveillance for polymorphisms and copy number as a monitoring tool to track the emergence and dynamics of Plasmodium falciparum drug resistance. A molecular baseline for Suriname was established in 2005, with P. falciparum chloroquine resistance transporter (pfcrt) and P. falciparum multidrug resistance (pfmdr1) markers and copy number in 40 samples. The baseline results revealed the existence of a uniformly distributed mutated gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
(54 reference statements)
5
10
0
Order By: Relevance
“…In this study, the N86 wild type was detected in almost all samples from periods 1 and 2, in agreement with earlier reports from Suriname [51] and other South American countries [53, 54]. Considering that in period 1 Brazilian national chemotherapy guidelines recommended three different therapeutic approaches, i.e., use of chloroquine, quinine and mefloquine, it is possible to conclude that drug pressure was not able to select a mutant genotype.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the N86 wild type was detected in almost all samples from periods 1 and 2, in agreement with earlier reports from Suriname [51] and other South American countries [53, 54]. Considering that in period 1 Brazilian national chemotherapy guidelines recommended three different therapeutic approaches, i.e., use of chloroquine, quinine and mefloquine, it is possible to conclude that drug pressure was not able to select a mutant genotype.…”
Section: Discussionsupporting
confidence: 91%
“…These findings have important implications for understanding drug resistance evolution when standard resistance alleles reach fixation and can lose their utility as markers because of adaptive changes at other amino acid positions or loci in the genome. In South America, the prevalence of the CQR marker K76T in the drug efflux transmembrane protein PfCRT has remained high, despite CQ having been abandoned for the treatment of P. falciparum infections (7)(8)(9). This situation contrasts with multiple settings in Africa, where the majority of molecular studies (10)(11)(12)(13) have documented an increase in the prevalence of WT pfcrt after CQ withdrawal.…”
mentioning
confidence: 56%
“…The finding in previous studies such as these that there was a decrease in the prevalence of the pfcrt 76T mutated allele and a re-emergence of CQ-sensitive strains some years after abandoning CQ was controversial, particularly as many studies in Africa documented an increase in the re-emergence of the wild type of pfcrt 76 after complete CQ withdrawal ( Laufer et al , 2006 ; Mohammed et al , 2013 ; Mbogo et al , 2014 ; Mekonnen et al , 2014 ). In contrast, South American isolates of P. falciparum have been reported to retain their mutated types despite the cessation of CQ use ( Vieira et al , 2004 ; Griffing et al , 2010 ; Adhin, Labadie-Bracho & Bretas , 2013 ). Similarly, studies conducted in Ethiopia have found a fixation of pfcrt 76T mutations after cessation of CQ use for more than a decade ( Mula et al , 2011 ; Golassa et al , 2014 ).…”
Section: Discussionmentioning
confidence: 97%